Development and programming of sismic resistant types BFP and RBS connections according to ANSI/AISC 358-16 (Gaceta Técnica, 2018)
Steel connections are a fundamental part in the design and construction process of metal structures. Making this connections design becomes an extensive mathematical procedure, which would generate delays manually due to the number of iterations necessary to obtain an adequate result. There are commercial programs that perform these procedures in an automated way, but their licenses tend to be very expensive, and emphasizing the above, this work has the purpose of creating a free and easy to use software for the design of BFP and RBS connections according to the guidelines established by the ANSI / AISC standard 358-2016. In addition, at the same time incorporate an additional tool for the teaching of matters related to connections in steel structures. The software is accompanied by a user manual that describes step by step some common examples of calculation, which can be used to teach the use of software. The results obtained by the program were compared with exercises developed by other authors, reflecting quite low percentages of difference and with them the acceptance of the results obtained with the program
Keywords: pre-qualified connection; interactive design; ANSI / AISC 358-16